"Pornografska literatura" V. Sorokina v primežu ruskega kulturnega spomina - Javornik, Miha (Primerjalna književnost, 2005)
The study concerns one of the most controversial Russian authors, the enfant terrible of modern Russian literature and culture, Vladimir Sorokin. Its purpose is to answer the question as to why his work - widely discussed by internationally renowned authorities in West European countries - has yet to become the subject of "academic" debate in Russia. The study looks for answers in the specifics of the Russian cultural model, and introduces the reader to the specifics of the post-Soviet cultural arena.
Keywords: Sorokin, Vladimir, 1955-; Russian literature; ruska književnost; ruska kultura; pornografska literatura; literarna recepcija